2023
DOI: 10.1021/acsami.3c01550
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Identification from AFM Images Using the IUPAC Nomenclature and Attribute Multimodal Recurrent Neural Networks

Abstract: Spectroscopic methods�like nuclear magnetic resonance, mass spectrometry, X-ray diffraction, and UV/visible spectroscopies�applied to molecular ensembles have so far been the workhorse for molecular identification. Here, we propose a radically different chemical characterization approach, based on the ability of noncontact atomic force microscopy with metal tips functionalized with a CO molecule at the tip apex (referred as HR-AFM) to resolve the internal structure of individual molecules. Our work demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Given the widespread use of DFT calculated energy profiles for the rationalization of on-surface reactions, 44,51–53 benchmarking theoretical energy profiles with highly accurate experimental values is an extremely important task for validating prevalent theoretical approaches. The availability of a trustworthy, sufficiently large database – either from experiment or theory – may eventually facilitate the use of machine learning in surface chemistry, just as it is currently conquering the identification of molecules from their SPM images 54 and other areas of chemistry. 55…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Given the widespread use of DFT calculated energy profiles for the rationalization of on-surface reactions, 44,51–53 benchmarking theoretical energy profiles with highly accurate experimental values is an extremely important task for validating prevalent theoretical approaches. The availability of a trustworthy, sufficiently large database – either from experiment or theory – may eventually facilitate the use of machine learning in surface chemistry, just as it is currently conquering the identification of molecules from their SPM images 54 and other areas of chemistry. 55…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Second, there is work on using ML models to identify chemical structure and determine nomenclature of molecules imaged by HR-AFM. , Auto-HR-AFM’s script can be modified to integrate these molecular identification techniques. By collecting the image inputs needed by these techniques– multiple molecules at a series of different heights,– we can identify molecules by name in real time.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of AFM imaging with Bayesian Inference and DFT calculations has been used to determine the adsorption configurations for a known molecule [46]. In previous work, we have demonstrated that it is possible to achieve a complete chemical identification of the structure and composition of a molecule from a 3D stack of constant-height HR-AFM images using two different approaches: (i) a Multimodal Recurrent Neural Network (M-RNN), that produces as output the IUPAC name of the molecule [47], and, (ii) a CGAN, that provides a 2D ball-and-stick model of the imaged molecule [48]. To the best of our knowledge, deep learning has not been used before to perform theoretical AFM simulations.…”
Section: Introductionmentioning
confidence: 99%
“…We find this analysis of a forward DL model for simulation of HR-AFM images to be also useful for better understanding how much physically relevant information about AFM imaging processes is encoded within the internal layers of the Convolutional Neural Network. This complementary view can help to further enhance inverse DL models, which are designed to extract the molecular structure from measured AFM data [42,47,48]. In particular, this forward model makes it easier to identify the most relevant data for the training, and to clearly spot information which is lost in the transformation.…”
Section: Introductionmentioning
confidence: 99%